PENERAPAN MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP N 1 TIGO NAGARI KABUPATEN PASAMAN - Ayu, Citra (STKIP Pesisir Selatan, 2018)
The low acquisition of mathematic concept for the seventh grade students in SMPN I Tigo Nagari Kabupaten Pasaman is a background of this research. This is because the process of learning has not involved the students optimally so that the students are not quite active and they tend receiving what they get from their teachers only. One of efforts to do is implementing Numbered Heads Together Learning Cooperative Model. The purpose of this research is to know whether the students’ mathematic concept acquisistion who use Numbered Heads Together Cooperative Learning Model is better than conventional one. This research was quasy experimental. The population of this research is all seventh grade students of SMPN I Tigo Nagari Kabupaten Pasaman. The data of this research is taken from final test of mathematic concept acquisition. The data analysis is done by t-test. Based on the result of data analysis and final test that the students’ acquisition of mathematic concept who use numbered Heads Together Cooperative Learning Model is better then conventional model